2018
DOI: 10.1002/fsn3.582
|View full text |Cite
|
Sign up to set email alerts
|

Local condiments from fermented tropical legume seeds modulate activities of critical enzymes relevant to cardiovascular diseases and endothelial function

Abstract: Investigation into modulatory effects of local condiments produced from fermented legume (African locust bean and soybean) seeds on activities of enzymes relevant to endothelial function and cardiovascular disease (arginase, phosphodiesterase‐5, acetylcholinesterase, and, ecto 5′‐nucleotidase) in vitro was the focus of this study. The condiments were prepared according to traditional methods of fermentation. Thereafter, modulatory effects of aqueous extracts from the condiments on activities of the enzymes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…In this case, as shown in Figure 3, all extracts analyzed in this study showed this characteristic of percentage inhibition, with emphasis on the SHE that obtained the highest percentage of inhibition (77.40%). Previous studies with the seed ethanolic extract of P. platycephala and aqueous from P. biglobosa, the latter defatted, confirm iAChE > 50% (Ademiluyi, 2018;Farias et al, 2013). Table 5 shows all the lethal concentrations of 50% of the extracts of P. platycephala.…”
Section: Anticholinesterase Activitymentioning
confidence: 77%
“…In this case, as shown in Figure 3, all extracts analyzed in this study showed this characteristic of percentage inhibition, with emphasis on the SHE that obtained the highest percentage of inhibition (77.40%). Previous studies with the seed ethanolic extract of P. platycephala and aqueous from P. biglobosa, the latter defatted, confirm iAChE > 50% (Ademiluyi, 2018;Farias et al, 2013). Table 5 shows all the lethal concentrations of 50% of the extracts of P. platycephala.…”
Section: Anticholinesterase Activitymentioning
confidence: 77%
“…Different parts of P. biglobosa such as seeds, bark, roots and flowers are reportedly used to treat myriads of diseases and ailments [11][12][13]. Scientific findings indicated that the condiments from fermented seeds of P. biglobosa control activities of certain enzymes relevant to cardiovascular diseases and endothelial function [14]. Generally, locust bean tree is used as source of firewood, charcoal and as timber for making pestles, mortars, bows, hoe handles, and seats while the husks and pods are good food for livestock [13,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%